2018
DOI: 10.3390/w10111601
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Efficiency of Diffuse Agricultural Pollution in a Constructed Wetland Impacted by Groundwater Seepage

Abstract: Diffuse agricultural pollution degrades water quality and is one of the main causes of eutrophication; therefore, it is important to reduce it. Constructed wetlands (CW) can be used as an effective measure for water quality improvement. There are two possible ways to establish surface flow CWs, in-stream and off-stream. We studied treatment efficiency of the in-stream free surface flow (FSW) Vända CW in southern Estonia from March 2017 until July 2018. The CW consists of two shallow-water parts planted with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Assessments of groundwater aquifers made in Portugal, Iran, Saudi Arabia, France, and other countries have shown that in many cases, nitrate (NO 3 − ) concentrations are exceeding the safe drinking water threshold of 50 mg NO 3 − L −1 , which is specified by the World Health Organization [3][4][5][6][7][8]. High NO 3 − concentrations in surface water and groundwater are causing environmental problems, such as eutrophication [9], and since NO 3 − becomes toxic to humans at concentrations of 50 mg NO 3 − L −1 and above, this relates to health issues like methemoglobinemia and cancer [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Assessments of groundwater aquifers made in Portugal, Iran, Saudi Arabia, France, and other countries have shown that in many cases, nitrate (NO 3 − ) concentrations are exceeding the safe drinking water threshold of 50 mg NO 3 − L −1 , which is specified by the World Health Organization [3][4][5][6][7][8]. High NO 3 − concentrations in surface water and groundwater are causing environmental problems, such as eutrophication [9], and since NO 3 − becomes toxic to humans at concentrations of 50 mg NO 3 − L −1 and above, this relates to health issues like methemoglobinemia and cancer [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…The VFCWs are planted with Phragmites Australis, with a density of 3 plants per m 2 . They have been included because of their great contribution to the removal and absorption of nutrients [23].…”
Section: Secondary Treatment Vertical Flow Constructed Wetland (Vfcw)mentioning
confidence: 99%
“…It is widely recognized that diffuse pollution is one of the major causes of poor water quality in surface waters [1,2]. An excess of nutrients in surface waters (mainly nitrogen and phosphorus) causes major environmental problems as eutrophication [3].…”
Section: Introductionmentioning
confidence: 99%
“…As an environmentally friendly natural treatment system, the CW has shown advantages over conventional techniques due to its low cost, good performance, and simple operation [7,9]. Recently, CW technology has also been used widely to treat rural runoff due to the easy maintenances and low energy demand [10][11][12]. These results show that CW has potential effects on nitrogen and phosphorus removal.…”
Section: Introductionmentioning
confidence: 99%
“…There are many mechanisms that are involved in nitrogen and phosphorus removal in CW including adsorption, precipitation, plants adsorption, and bacteria transformation during the rural rain runoff treatment processes in CW [9,10]. Biological nitrification and denitrification are regarded as the important removal mechanisms for nitrogen removal in CW, while the other mechanisms, including plant and substrate adsorption, are also important [11].…”
Section: Introductionmentioning
confidence: 99%